Development of geo-tagging video app to assist road development projects in the Philippines. Issue 2 (1st September 2017) - May, Adam; Wilson, Gary; Pym, Andrew
Abstract : The Philippines consists of over 7000 separate islands, of which around 2000 are populated. In a drive to promote economic growth and prosperity, the government, together with the World Bank, is investing heavily in road building. In order to realise the strategic vision for this road investment programme, the following major challenges were identified. ( a ) The Philippines road network is extensive yet fragmented, and falls under the responsibility of many levels of government. ( b ) There is currently no comprehensive mapping of the road network. ( c ) Historically, road investment has been opaque and highly politicised, with poor governance and corruption undermining delivery. Good financial governance without visibility or transparency is almost impossible to achieve. Smartphones were chosen as the tool to provide the required levels of accountability needed for large-scale infrastructure investment projects. Using the built-in video recording and global positioning system capabilities of these widely available devices, the major investors were able to see exactly where and why road building is needed and to monitor how their money is spent. This innovative solution has proven to be a success and is now being considered as the template for how similar investments can be monitored in countries of a similar nature.